A cross-sectional survey of farmer reported prevalence and farm management practices associated with neonatal infectious arthritis (“joint ill”) in lambs, on UK sheep farms - Jackson, L. P.; Higgins, H. M.; Duncan, J. S. (Frontiers in Veterinary Science, 2024)
IntroductionNeonatal infectious arthritis (NIA) is a bacterial disease of lambs in the first month of life. NIA is associated with poor animal welfare, economic losses, and prophylactic antibiotic use. Farmers report problems with NIA despite following current guidance on prevention. The aim of this study was to estimate NIA UK incidence, describe current management practices for NIA control, and farm management risk factors associated with NIA.MethodsA cross-sectional, online questionnaire of UK sheep farmers was carried out between June and October 2020. Descriptive statistics, and univariable and multivariable risk factor analysis was undertaken.ResultsOf the 322 respondents, 64% reported joint ill cases in the 2020 lambing period. The median within flock incidence was 1.4% (IQR 0.8–2.6%; 95% CI, 1.2–1.6). Seventeen percent of farmers estimated their current treatment efficacy for NIA was less than 50%. Eleven percent of farmers used prophylactic or metaphylactic antibiotics in all lambs to prevent NIA occurrence. Across all flocks, risk factor associated with NIA occurrence was the number of ewes lambed (301–600; OR, 3.9; 95% CI 1.9–8.0. >600; OR, 13.7; 95% CI, 5.4–34.4). In outdoor lambing flocks, increased risk of joint ill was associated with the number of ewes lambed (>600 ewes; OR, 34.7; 95% CI, 6.6–182.7), not providing outdoor shelter to lambing ewes (OR, 3.0; 95% CI, 1.2–7.8), and not cleaning ear tags (OR, 5.7; 95% CI, 1.5–21.4). Using antibiotics as a preventative measure was associated with a reduced risk of joint ill (OR, 0.1; 95% CI, 0.01–0.4). In indoor lambing flocks, increased risk of joint ill was associated with upland flocks (OR, 3.0; 95% CI, 1.3–6.8), number of lambs born alive (501–1,000; OR, 4.1; 95% CI, 1.6–10.7. >1,000; OR, 14.0; 95% CI, 4.0–48.9), and not washing hands (OR, 3.6; 95% CI, 1.2–10.6).ConclusionNIA was reported in indoor and outdoor lambing flocks. A pattern of risk factors associated with increasing intensity of lambing was observed. Prophylactic antibiotic use was associated with a reduced risk of NIA in outdoor flocks, however, NIA still occurred in flocks where this was practiced. More veterinary involvement is advised in the diagnosis, treatment protocols, and prevention of NIA.